The Local in the Global: Agriculture, State and Revolution in Iran - Araghi, Farshad (The International Journal of Sociology of Agriculture and Food, 2021)
This article examines state and class restructuring in late nineteenth century Iran in connection with the reorganization of world agriculture under the “Second Colonialism.” Seeing the local within the global and vice versa, and linking economy, polity, and culture, I provide an alternative interpretation of the nature of nationalism in late nineteenth century Iran. I show that the relations of the Iranian state and the mercantile classes with the world market led to contradictory developments. Export cropping opened to merchants new opportunities for expanding their economic horizons. As they gained financial strength, they articulated and asserted their interests. At the same time, however, the Iranian state was being internationalized, as it increasingly represented the political and commercial interests of colonial powers. The domestic “contraction” of the state and the “expansion” of national commercial classes created tension between the state and the merchant bourgeoisie who, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European colonialism. Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for struggle for the nationalization of the state. Hence, nationalism and modernity in Iran took a nonsecular character.